2021
DOI: 10.1002/jbm.a.37177
|View full text |Cite
|
Sign up to set email alerts
|

Microneedle based adipose derived stem cells‐derived extracellular vesicles therapy ameliorates UV‐induced photoaging in SKH‐1 mice

Abstract: Extracellular vesicles from adipose derived stem cells (ADSCs‐EVs) have shown immunomodulation and anti‐photoaging effects; however, the skin barrier prevents their absorption via skin. Meanwhile, microneedle (MN) is a widely used and minimally invasive tool for dermal delivery of drugs, it also has neocollagenesis effect by creating tiny injuries and initiating wound healing process. To investigate the effect of MN combined with ADSCs‐EVs on skin aging, photoaging in SKH‐1 mice was induced by chronic exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…A study by Cao et al (2021) demonstrated that the addition of EVs could enhance collagen density and organisation when compared to microneedling alone. However, the study lacked EV only controls, so the added benefit of microneedling could not be determined [17]. An alternative approach could be via the local injection of EVs.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…A study by Cao et al (2021) demonstrated that the addition of EVs could enhance collagen density and organisation when compared to microneedling alone. However, the study lacked EV only controls, so the added benefit of microneedling could not be determined [17]. An alternative approach could be via the local injection of EVs.…”
Section: Tablementioning
confidence: 99%
“…Additionally, EVs can act as carriers for a wide range of chemical and biological drugs, enhancing cellular targeting and uptake. While the combined delivery of EVs with adjunct therapies such as microneedling or through association with biocompatible scaffolds offers the opportunity to further enhance delivery across the skin barrier and modulate their release kinetics to enhance clinical outcomes [17]. To date, the majority of published outcomes have been observed through the delivery of mesenchymal stem cell-derived EVs (MSC-EVs), with this cell source offering benefits in the translation of EV therapies due to their immunoregulatory effects and ability to be sourced allogeneically.…”
Section: Introductionmentioning
confidence: 99%
“…It allows drugs to directly reach the dermal tissue by creating plenty of microholes to bypass the stratum corneum barrier [ 88 ]. Cao et al found that a combination of microneedle and ADSC-EVs exhibited promising anti-aging effects in photoaging skin in vivo, as indicated by the least wrinkles, the maximum collagen density, and the most organized collagen fibers compared to the other groups [ 89 ]. There is also a decrease in epidermal thickness and improved skin barrier function with higher stratum corneum hydration values and lower trans-epidermal water loss (TEWL).…”
Section: Advanced Delivery Strategy For Evsmentioning
confidence: 99%
“…Because of the existence of the skin barrier, simply applying EVs to the skin surface will sharply reduce its effectiveness. Studies have shown that ADSC-EVs combined with a microneedle roller can effectively reduce the aging phenotype of SKH-1 mice [ 167 ], but this method of promoting EV absorption could easily increase skin sensitivity. And in recent years, the microneedle patch has become a research hotspot in the field of dermatology based on its advantages of minimal invasiveness, painlessness, and high drug loading.…”
Section: Evs In Aging-related Diseasesmentioning
confidence: 99%